2016
DOI: 10.1007/s11095-016-1971-8
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and Efficacy of Low Temperature-Sensitive Liposome Encapsulated Docetaxel Combined with Mild Hyperthermia in a Mouse Model of Prostate Cancer

Abstract: This technique of hyperthermia sensitization and enhanced docetaxel delivery has potential for clinical translation for prostate cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Therefore, although the first or second generation of liposomes displayed improved pharmacokinetics (ie, decreased clearance and higher tumor accumulation), [12][13][14] further development of nanoparticles is still an ongoing story with taxanes. Thus, more sophisticated forms have been developed such as co-loaded liposomes (eg, docetaxel + palmitoyl ascorbate, 15 paclitaxel + rapamycin, 16 docetaxel + BCL-2 SiRNA 17 ), triggered liposomes (eg, pH sensitive 18 or thermosensitive 19 ) and targeted liposomes. Many moieties (eg, small-molecule ligands, peptides 20 and monoclonal antibodies) have been used over the last years to actively target cancer cells through different strategies, including targeting several receptors like folate receptors, 21,22 integrin 23 and transferrin.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, although the first or second generation of liposomes displayed improved pharmacokinetics (ie, decreased clearance and higher tumor accumulation), [12][13][14] further development of nanoparticles is still an ongoing story with taxanes. Thus, more sophisticated forms have been developed such as co-loaded liposomes (eg, docetaxel + palmitoyl ascorbate, 15 paclitaxel + rapamycin, 16 docetaxel + BCL-2 SiRNA 17 ), triggered liposomes (eg, pH sensitive 18 or thermosensitive 19 ) and targeted liposomes. Many moieties (eg, small-molecule ligands, peptides 20 and monoclonal antibodies) have been used over the last years to actively target cancer cells through different strategies, including targeting several receptors like folate receptors, 21,22 integrin 23 and transferrin.…”
Section: Introductionmentioning
confidence: 99%
“…123 Mild hyperthermia of solid tumors could also increase drug delivery efficiency. 128,129 Homogenous near-infrared light exposure of solid tumors has been shown to enhance homogeneous delivery of an antibody−photoabsorber conjugate in solid tumors, resulting in improved therapeutic efficacy in treating head and neck cancer with photoimmunotherapy. 130 The tumor microenvironment plays a key role in the proliferation, invasion, and metastasis of aggressive tumors.…”
Section: ■ Future Perspectives Of Drug Delivery In Cancer Therapymentioning
confidence: 99%
“…It has been shown that pharmacologically induced hypertension could improve drug delivery into solid tumors . Mild hyperthermia of solid tumors could also increase drug delivery efficiency. , Homogenous near-infrared light exposure of solid tumors has been shown to enhance homogeneous delivery of an antibody–photoabsorber conjugate in solid tumors, resulting in improved therapeutic efficacy in treating head and neck cancer with photoimmunotherapy …”
Section: Future Perspectives Of Drug Delivery In Cancer Therapymentioning
confidence: 99%
“…Hyperthermia is a therapeutic technique in which a body is subjected to mild increases in temperature (41-45 C) for an extended length of time (15-90 min) [1][2][3][4][5]. An increase in temperature affects many biological phenomena, including blood flow oxygenation and the permeability of nanoparticles [1,6].…”
Section: Introductionmentioning
confidence: 99%